Metodologi Penyusunan dan Kedudukan Pedagogis Kitab “Mughni al-Labib” Karya Ibnu Hisyam: - - Kholifiatul Masito; Mohammad Pribadi; Gilang Inggit Maulana (Ihtimam : Jurnal Pendidikan Bahasa Arab, 2024)
Ibnu Hisham is a famous Nahwu scholar in Egypt. His wisdom is recognized by scholars of his time even today. Not a few of his essays have been studied by Arabic language scholars, including Mughni al-Labib. Mughni al Labib is a Nahwu book written to make things easier for those studying i'rab or changes in the endings of words in Arabic grammar. This research uses a descriptive-qualitative approach with emphasis on literature review. The research steps or methods are to listen and take notes. The results of this research are; First, in compiling the book, Ibnu Hisyam divided it into eight chapters, and one of the discussion methods used by Ibnu Hisyam was a comparative analysis of the previous Nahwu school. Furthermore, regarding the book's pedagogical position for I'rab scholars, it is not a simple book that can be read by beginners. This is due to the application of the rules of i'rab which are directly applied to the verses of the Qur’an